Motivace a odměňování pracovníků ve vybrané společnosti - Večeřová, Nikola (Vysoké učení technické v Brně. Fakulta podnikatelská, 2019)
Diplomová práce je zaměřena na motivaci a odměňování pracovníků ve vybraném podniku. Zabývá se analýzou motivačního a odměňovacího systému společnosti Lidl Česká republika, v. o. s. Cílem je navrhnout změny a doporučení na zlepšení situace podniku do budoucna. Teoretická část je zaměřena na vymezení pojmů motivace, přehled základních motivačních teorií, odměňování a zaměstnanecké benefity. Praktická část obsahuje charakteristiku a představení vybrané společnosti, analýzu a zhodnocení současného systému. V závěru práce je na základě zjištěných výsledků provedeno shrnutí, jsou zde uvedeny návrhy a doporučení.

The thesis is focused on the motivation and remuneration of employees in the selected company. It investigates in an analysis of the motivational and remuneration system of a company Lidl Česká republika, v. o. s. The aim is to find changes and recommendations for improving situation of company in the future. The theoretical part of dissertation explains meaning of a motivation, basic motivational theories, remuneration and employee benefits. The practical part describes characteristics of the company that I have chosen. It also includes an analysis and evaluation of the current system. In the conclusion of the dissertation is a summary based on results that have been done and there are also suggestions and recommendations.
Motivation and Remuneration of the Employees in a Selected Company
Keywords: Motivace; motivační teorie; odměňování; benefity; společnost; dotazníkové šetření; analýza; Motivation; motivational theory; remuneration; benefits; company; questionnare; analysis